The Political Translations of Monteiro Lobato and Carlos Lacerda - Milton, John; Euzebio, Eliane (Meta, 2004)
AbstractThis article examines the connection between translation and politics, concentrating on a specific period in Brazilian history, the dictatorship of Getúlio Vargas, from 1930 to 1945, and then from 1950 to 1954. It initially looks at the link between fiscal policy and translation. It then analyzes the translations, or rather, adaptations, of Peter Pan and Don Quixote, by the Brazilian writer and publisher, Monteiro Lobato. The final section of the paper will describe the situation surrounding the translation of Shakespeare’s Julius Caesar by the Brazilian politician, Carlos Lacerda, governor of the state of Guanabara (greater Rio de Janeiro) (1960-1965).